Snowmobiling in Maine: Past Successes, Future Challenges - Vail, David (Maine Policy Review, 2002)
With one snowmobile registration for every 15 residents, Maine may well have the most snowmobiles per capita of any U.S. state. Moreover, the state’s 12,000-mile network of groomed trails and its 2,500-mile Interconnected Trail System make it a major winter tourist attraction. Still, as David Vail points out—and as the number of snowmobile-related deaths confirms—such progress has not come without costs and conflict. Although Vail argues the benefits outweigh the costs, he suggests Maine should act now to alleviate the conflicts related to congestion, over use of the state’s major trails, noise and air pollution, and free riding by non-dues-paying sledders. He argues these problems cannot be handled by local snowmobile clubs alone, but require an active partnership with state government to mitigate current conflicts and to avert future ones.